PENGARUH KUALITAS PRODUK DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN LAMPU LED PHILIPS (STUDI KASUS PADA WILAYAH KECAMATAN CIKARANG TIMUR) - Andari Ratna Widyastuti, Trie; Radhiya Salsabila, Kus (JAMBIS : Jurnal Administrasi Bisnis, 2023)
This  study aims  to  determine the effect of  product quality and  price on  purchasing decisions. This  study uses  a  quantitative approach. Data retrieval techniques with  research instruments used are  in the  form of   questionnaires and  literature. Sampling technique in this  study is Non- probability sampling the  sample of  this  study is   the  Philips lamp users in  the  district of  East Cikarang, Central Jakarta and  obtained 150 respondents. Data analysis using multiple linear regression. In   this study the authors used SPSS  26.The results of  this  study showed that  the product quality (X1) there is a partial and  significant influence on  the  purchase decision (Y)   on Philips LED  lamps by  72.7%. Price (X2) has  a partial and  significant influence on   the  purchase decision (Y)  on  Philips LED  lamps by  66.1%. Other results, that  together the  product quality (X1) and  price (X2) there is a significant influence on   the purchase decision (Y)  on   Philips LED lights by  80.2% and  the rest is influenced by  other factors outside the model of this  study that was  not studied by the researcher